Association between erectile dysfunction and chronic periodontitis: A clinical study - Ranjit Singh Uppal; Rajat Bhandari; Karanparkash Singh (Wolters Kluwer Medknow Publications, 2014)
Background: In recent years, evidence has come forth supporting the notion that localized infectious diseases such as periodontal disease may indeed influence a number of systemic diseases. Erectile dysfunction (ED) and chronic periodontitis have common risk factors such as diabetes mellitus, cardiac diseases and smoking etc. Aim: The aim was to evaluate the periodontal status of the subjects suffering from ED and to find association between vasculogenic ED and chronic periodontitis, if any. Study Design: A total of 53 subjects suffering from vasculogenic ED were enrolled for the study and were divided into three groups on the basis of severity of ED. Materials and Methods: The clinical (probing pocket depth) and radiographic parameters (alveolar bone loss) were recorded and periodontal status of three groups was evaluated, compared and an attempt was made to find an association between ED and chronic periodontitis. Karl Pearson's correlation was used to assess an association between the two conditions. Statistical Analysis: One-way ANOVA and Scheffe's test were used to find the significant difference of chronic periodontitis with severity of ED. Karl Pearson's correlation was used to find an association between chronic periodontitis and ED. Results: Statistically significant mean differences of 1.73 mm, 0.56 mm and 1.17 mm were recorded when comparison was made among Group I and III, Group I and II and Group II and III, respectively. Mean differences in bone loss among three groups were also statistically significant. Both the diseases were positively correlated to each other. Conclusion: It may be concluded that chronic periodontitis and ED are associated with each other. However, further large scale studies with confounder analysis and longitudinal follow-up are warranted to explore the link between these two diseases.